Implementation of Faraidh's Provisions in Hibah Wasiat (A Case in South Banjar Kalimantan) - Wahidah, Wahidah; Azhar, Alias (al-'adalah, 2019)
This research illustrates the practice of inheritance in the Banjar community of South Kalimantan. The aim is to see the extent to which the provisions of Islamic inheritance law (farāidh) are applied by the member of society in everyday life. This phenomenon is revealed through several field research methods, especially in-depth interviews, the results of which are then analyzed to obtain conclusions. This study found the fact that although in general, the majority of Banjar people of South Kalimantan resolved their inheritance cases by farāidh (Islamic inheritance law), there was a tendency for some citizens to put forward the spirit of "Badamai (Keeping Peace)" to bring up ways of resolving inheritance cases that seemed varied and unique. In such a model, the formulation of the inheritance distribution specified in the farāidh is not fully implemented but is modified through the hibah wasiat (testamentary grant) method. In the case of ashābah bi al-ghair (heirs of a different gender), the pattern of division of "two to one" is not carried out by the mushi (testator)  because of certain reasons/considerations related to the real condition of the heirs (economic level, marital status, age, etc).